High expression of podoplanin in squamous cell carcinoma of the tongue occurs predominantly in patients ≤40 years but does not correlate with tumour spread. (9th October 2015) - Sgaramella, Nicola; Lindell Jonsson, Eva; Boldrup, Linda; Califano, Luigi; Coates, Philip J; Tartaro, Gianpaolo; Lo Muzio, Lorenzo; Fåhraeus, Robin; Colella, Giuseppe; Dell'Aversana Orabona, Giovanni; Loljung, Lotta; Santagata, Mario; et al.
Abstract: More than 30% of patients with squamous cell carcinoma (SCC) of the mobile tongue have clinically undetectable lymph node metastasis. Tumour cells can spread as single cells or collectively. A protein known to play a role in both processes is podoplanin, which is expressed in endothelial cells not only in lymph vessels but also in some aggressive tumours with high invasive and metastatic potential. Here we studied samples from 129 patients with primary SCC of the tongue for expression of podoplanin using immunohistochemistry. mRNA levels were analysed in another 27 cases of tongue SCC with adjacent clinically tumour‐free tongue tissue and 14 tongue samples from healthy donors. Higher levels of podoplanin were seen in tumours compared to both normal tongue and clinically normal tongue in the tumour vicinity. No association was found between levels of podoplanin, presence of lymph node metastases or other clinical factors. Patients aged 40 or less were more likely to express high levels of podoplanin protein compared to older patients ( p = 0.027). We conclude that levels of podoplanin in primary tongue SCCs are not associated with lymph node metastases. However, tongue SCCs arising in young patients (≤40 years of age) are more likely to express high levels of podoplanin than tongue SCCs that arise in the more elderly. The data suggest that podoplanin has a distinctive role in young patients, who are known to have a poor prognosis: these patients may, therefore, benefit from podoplanin inhibitory therapies.